PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KPP PRATAMA MAKASSAR UTARA - Fitriadi, Fitriadi (Restitusi : Jurnal Riset Perpajakan, 2022)
This study aims to analyze the effect of understanding tax regulations on taxpayer compliance and tax sanctions on taxpayer compliance. The research was conducted at the North Makassar Tax Office, with a research sample of taxpayers registered at the North Makassar Tax Office. The results of the study indicate that the understanding of tax regulations has a positive and significant effect on taxpayer compliance, as well as tax sanctions that have a positive and significant effect on taxpayer compliance.